Metal-clad laminate and method for manufacturing metal-clad laminate
Through the heating and pressurization process under vacuum environment, combined with a specific layering method, the problems of LCP film anisotropy and metal foil bonding are solved, and high-strength, low warpage and high-precision metal-covered laminated body are manufactured.
Patent Information
- Application Number
- CN202411227594.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-04
- Filing Date
- 2024-09-03
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art has shortcomings in improving the anisotropy of the thermoplastic liquid crystal polymer (LCP) film and bonding the metal foil to the LCP film with high strength, resulting in problems such as reducing the resin strength of the LCP laminated film and warping and solder reflow in the metal laminated plate.
The accumulated precursor is heated under a vacuum environment, and the accumulated precursor is pressurized during the cooling process by using the pressurization process. Combined with a specific accumulation method and heater configuration, the anisotropy of the LCP film and the peel strength between the metal foil and the LCP film is improved.
The anisotropy of the LCP laminated film is improved, the bonding strength between the metal foil and the LCP film is improved, the warping amount and void generation are reduced, and the resin strength and dimensional accuracy of the metal-covered laminated body are improved.
Smart Images

Figure CN119550631A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a metal-clad laminate in which a liquid crystal polymer film and a metal foil are laminated, and a method for producing the metal-clad laminate. Background Art
[0002] The demand for equipment used in the fifth generation communication (5G) system is increasing. Therefore, as a material with low high-frequency transmission loss, attention is paid to thermoplastic liquid crystal polymer (LCP; Liquid Cristal Polymer) film. Hereinafter, liquid crystal polymer is referred to as "LCP".
[0003] LCP is a polymer in which the molecular chains are arranged in one direction in a molten state and show liquid crystal properties. The molecular chains are oriented along the melt extrusion direction (MD) when the LCP film is made. Due to the orientation of the molecular chains, the tensile strength of MD is lower than that of the perpendicular direction (TD), the linear expansion coefficient is higher, and anisotropy becomes a problem. Therefore, for example, Patent Document 1 describes a method for manufacturing a multiaxially oriented laminate, wherein the method for manufacturing the multiaxially oriented laminate changes the directions of multiple sheets of thermotropic liquid crystal polymers that are substantially oriented in one direction and thermally bonds them integrally.
[0004] For example, Patent Document 2 describes a method for producing a metal-clad laminate by roll-to-roll, wherein the laminate is a laminate of a thermoplastic liquid crystal polymer film and a metal sheet. Prior art literature Patent Literature
[0005] [Patent Document 1] Japanese Patent Application Laid-Open No. 58-31718 [Patent Document 2] International Publication No. 2017 / 154811 Summary of the invention Technical problem to be solved by the invention
[0006] The following analysis is given from the viewpoint of the present disclosure.
[0007] In the method for producing a multiaxially oriented laminate described in Patent Document 1, two LCP films are joined under atmospheric pressure. However, the improvement of anisotropy is insufficient for heating and joining under atmospheric pressure. In addition, the voids generated in the obtained LCP laminated film cause the resin strength of the LCP laminated film to be greatly reduced. In addition, Patent Document 1 does not record or teach the joining of metal foil to the multiaxially oriented laminate and the metal-clad laminate to which the metal foil is joined.
[0008] The manufacturing method of the metal-clad laminate described in Patent Document 2 cannot improve the anisotropy of the LCP film. In Patent Document 2, if the anisotropy of the LCP film is improved before manufacturing the metal-clad laminate, another process is required, resulting in a method for manufacturing the metal-clad laminate with low production efficiency. In addition, since the metal-clad laminate manufactured by the manufacturing method of the metal-clad laminate described in Patent Document 2 does not undergo a pressurization process, the peel strength between the metal foil and the LCP film cannot be improved. Furthermore, since the roll-to-roll method of Patent Document 2 does not undergo a pressurization process, the manufactured metal-clad laminate has a warpage of more than 3 mm, which causes a problem of obstruction in the transportation of the printed circuit board in the solder reflow process.
[0009] Therefore, it is desirable to provide a method for producing a metal-clad laminate that can bond a metal foil to an LCP film with high strength while improving the anisotropy of the LCP film. Technical means to solve technical problems
[0010] According to a first aspect of the present invention, a method for manufacturing a metal-coated laminate is provided, the manufacturing method comprising: a lamination step, in which a lamination precursor of a first liquid crystal polymer film, a second liquid crystal polymer film and a first metal foil is laminated in a manner in which the surface of the first liquid crystal polymer film and the surface of the second liquid crystal polymer film are directly opposite to each other; a heating step, in which the lamination precursor is heated at a temperature 15°C to 45°C higher than a first melting point for 1 minute to 60 minutes in an environment with a vacuum degree of less than 200 hPa, wherein the first melting point is the higher melting point of the melting points of the first liquid crystal polymer film and the second liquid crystal polymer film; and a pressurizing step, in which cooling is started after the heating step is completed, and the lamination precursor is pressurized in a lamination direction at a first pressure of 0.5 MPa to 5 MPa. In the lamination step, the first liquid crystal polymer film and the second liquid crystal polymer film are laminated so that the extending direction of the first liquid crystal polymer film and the extending direction of the second liquid crystal polymer film form an angle of 80° to 100°.
[0011] According to the second aspect of the present invention, a metal-coated laminate is provided, which comprises a second liquid crystal polymer layer, a first liquid crystal polymer layer and a first metal layer in sequence, the peel strength between the first liquid crystal polymer layer and the first metal layer is 0.9 kN / m to 2.5 kN / m, the orientation (MD / TD ratio) of the laminated film composed of the first liquid crystal polymer layer and the second liquid crystal polymer layer is 1.0 to 1.2, and the resin strength of the laminated film is greater than 100 MPa, and the warping amount is less than 3 mm.
[0012] According to a third aspect of the present invention, a metal-coated laminate is provided, which comprises a second metal layer, a second liquid crystal polymer layer, a first liquid crystal polymer layer and a first metal layer in sequence, the peel strength between the first liquid crystal polymer layer and the first metal layer is 0.9 kN / m to 2.5 kN / m, the peel strength between the second liquid crystal polymer layer and the second metal layer is 0.9 kN / m to 2.5 kN / m, the orientation (MD / TD ratio) of the laminated film composed of the first liquid crystal polymer layer and the second liquid crystal polymer layer is 1.0 to 1.2, and the resin strength of the laminated film is greater than 100 MPa, and the warping amount is less than 3 mm. Beneficial Effects
[0013] According to the method for producing a metal-clad laminate of the present disclosure, it is possible to produce a metal-clad laminate having an LCP laminate film having improved anisotropy.
[0014] According to the method for producing a metal-clad laminate of the present disclosure, the step of improving anisotropy and the step of bonding the metal foil to the LCP laminate film can be performed simultaneously.
[0015] According to the method for manufacturing a metal-clad laminate of the present disclosure, it is possible to manufacture a metal-clad laminate having high dimensional accuracy while having high bonding strength and high resin strength.
[0016] According to the manufacturing method of the metal-clad laminated body disclosed in the present invention, the laminated precursor has more than two first laminated units, and the first laminated units laminated the second liquid crystal polymer film, the first liquid crystal polymer film and the first metal foil in sequence, and a thin planar heater is arranged between the adjacent first laminated units and the first laminated units. By using the laminated precursor, uneven heating temperature will not occur, and a significant improvement in productivity can be achieved.
[0017] According to the manufacturing method of the metal-clad laminated body disclosed in the present invention, the laminated precursor has two or more second laminated units, and the second laminated units laminated the second metal foil, the second liquid crystal polymer film, the first liquid crystal polymer film and the first metal foil in sequence. The laminated precursor having a thin planar heater is arranged between adjacent second laminated units and the second laminated units. By using the laminated precursor, uneven heating temperature will not occur, and a significant improvement in productivity can be achieved.
[0018] The metal-clad laminate disclosed in the present invention is a high-quality metal-clad laminate having high bonding strength and high resin strength, high dimensional accuracy, little generation of voids, and small warpage. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] [ Figure 1 ] Figure 11 is a flowchart showing an example of a process flow in the method for manufacturing the metal-clad laminate according to the first embodiment of the present disclosure. [ Figure 2 ] Figure 2 1 is a schematic side view showing an example of a laminate precursor. [ Figure 3 ] Figure 3 is a schematic side view showing another example of a laminate precursor. [ Figure 4 ] Figure 4 It is a schematic diagram for explaining the method for manufacturing the metal-clad laminate according to the first embodiment. [ Figure 5 ] Figure 5 It is a schematic diagram for explaining the method for manufacturing the metal-clad laminate according to the first embodiment. [ Figure 6 ] Figure 6 Schematic diagram showing an example of a laminate precursor having a multilayer structure. [ Figure 7 ] Figure 7 FIG. 1 is a schematic diagram showing another example of a laminate precursor having a multilayer structure. [ Figure 8 ] Figure 8 1 is a schematic diagram showing an example of the metal-clad laminate of the present disclosure. [ Fig. 9 ] Fig. 9 1 is a schematic diagram showing another example of the metal-clad laminate of the present disclosure. DETAILED DESCRIPTION
[0020] Preferred aspects of the above-mentioned viewpoints are described below.
[0021] According to a preferred method of the first viewpoint mentioned above, the process includes an annealing step, in which a first pressure is reduced to a second pressure that is 1 / 2 to 1 / 20 of the first pressure within a temperature range from a first glass transition temperature to a first melting point, and the temperature range and the second pressure are maintained for 5 to 60 minutes, wherein the first glass transition temperature is the lower glass transition temperature of the glass transition temperatures of the first liquid crystal polymer film and the second liquid crystal polymer film.
[0022] According to a preferred embodiment of the first aspect, the melting point of the first liquid crystal polymer film and the melting point of the second liquid crystal polymer film are both within a range of 270° C. to 340° C.
[0023] According to a preferred embodiment of the first aspect, the first liquid crystal polymer film and the second liquid crystal polymer film are made of the same material.
[0024] According to a preferred embodiment of the first aspect, the ten-point average roughness of the surface of the first metal foil facing the first liquid crystal polymer film is 1.5 μm or less.
[0025] According to a preferred embodiment of the first aspect, the first metal foil is an electrolytic copper foil or a rolled copper foil having a thickness of 3 μm to 40 μm.
[0026] According to a preferred embodiment of the first aspect, in the produced metal-clad laminate, the peel strength between the first liquid crystal polymer film and the first metal foil is 0.9 kN / m to 2.5 kN / m.
[0027] According to a preferred embodiment of the first aspect, in the lamination step, a lamination precursor is produced in a mold. In the pressurizing step, the lamination precursor is pressurized while being molded by the mold.
[0028] According to a preferred embodiment of the first aspect, the laminate precursor further comprises a second metal foil. In the lamination step, the first liquid crystal polymer film and the first metal foil are arranged to face each other directly. The second liquid crystal polymer film and the second metal foil are arranged to face each other directly.
[0029] According to a preferred embodiment of the first aspect, the second metal foil is an electrolytic copper foil or a rolled copper foil having a thickness of 3 to 40 μm, and the ten-point average roughness of the surface of the second metal foil facing the second liquid crystal polymer film is 1.5 μm or less.
[0030] According to a preferred embodiment of the first aspect, in the produced metal-clad laminate, the peel strength between the second liquid crystal polymer film and the second metal foil is 0.9 kN / m to 2.5 kN / m.
[0031] According to a preferred embodiment of the first viewpoint, the laminate precursor has two or more first laminate units, wherein the first laminate units laminate the second liquid crystal polymer film, the first liquid crystal polymer film and the first metal foil in sequence, and a thin planar heater is arranged between adjacent first laminate units.
[0032] According to a preferred embodiment of the first viewpoint described above, the laminated precursor has two or more second laminated units, wherein the second laminated units laminate a second metal foil, a second liquid crystal polymer film, a first liquid crystal polymer film and a first metal foil in sequence, and a thin planar heater is arranged between adjacent second laminated units and second laminated units.
[0033] According to a preferred embodiment of the first aspect, the thin planar heater can be heated to 300° C. or higher.
[0034] According to a preferred embodiment of the second and third aspects, the laminate film has a thickness of 10 cm 2The average number of voids having an area diameter of 0.5 mm or less is 5 or less.
[0035] According to a preferred embodiment of the second and third aspects, the ratio of the linear expansion coefficients in the plane direction (MD / TD) of the laminate film is 1.2 or less, and the linear expansion coefficient in the thickness direction (z direction) is 45 ppm or less.
[0036] According to a preferred embodiment of the second aspect and the third aspect, the first metal layer and the second metal layer are electrolytic copper layers or rolled copper layers having a thickness of 3 μm to 40 μm.
[0037] According to a preferred embodiment of the second and third aspects, the metal-clad laminate is used for a flexible printed circuit board or a rigid printed circuit board.
[0038] A method for producing the metal-clad laminate according to the first embodiment of the present disclosure will be described. Figure 1 1 is a flowchart showing an example of a process flow in the method for producing a metal-clad laminate according to the first embodiment of the present disclosure. Hereinafter, the process flow in the method for producing a metal-clad laminate according to the present invention will be described.
[0039] In step S11 (lamination process), lamination is performed so that the surface of the first liquid crystal polymer film and the surface of the second liquid crystal polymer film in the lamination precursor directly face each other, and the process shifts to S12.
[0040] In step S12 (heating process), heating is performed at a temperature 15° C. to 45° C. higher than the first melting point for 1 minute to 60 minutes in an environment with a vacuum degree of 200 hPa or less, and the process is then transferred to S13 .
[0041] In step S13 (pressurizing step), cooling is started after the heating step is completed, and the lamination precursor is pressurized in the lamination direction at a first pressure of 0.5 MPa to 5 MPa, and the process is transferred to S14.
[0042] In step S14 (annealing process), the first pressure is reduced to the second pressure within the temperature range of the first glass transition temperature to the first melting point, and the state of the temperature range and the second pressure is maintained for 5 minutes to 60 minutes, thereby completing the present treatment.
[0043] From the above, the method for manufacturing a metal-clad laminate according to the first embodiment of the present disclosure can manufacture a metal-clad laminate having high dimensional accuracy while having high bonding strength and high resin strength.
[0044] The metal-clad laminate described in the present disclosure refers to a laminate of an LCP laminate film and a metal foil. The LCP laminate film described in the present disclosure is a film in which at least two LCP films are laminated and melted to form an integrated whole. In the LCP laminate film, the number of laminated LCP films may be, for example, 2, 3 or 4. In the metal-clad laminate of the present disclosure, the metal foil is laminated on at least one surface of the LCP laminate film. The metal foil may also be laminated on both surfaces of the LCP laminate film. The metal-clad laminate of the present disclosure may also be a multilayer structure in which LCP laminate films and metal foils are alternately laminated.
[0045] In the metal-clad laminate of the present disclosure, the directly superimposed LCP films are bonded (fused) to each other. The directly superimposed LCP films and the metal foil are bonded with high strength.
[0046] A schematic side view of a laminate precursor of the first embodiment is shown in Figure 2 The laminate precursor 10 described in the present disclosure refers to a laminate precursor before the metal-clad laminate is manufactured, and the laminate precursor 10 is obtained by laminating at least two LCP films (LCP film 1 and LCP film 2 ) and at least one metal foil 3 .
[0047] The first LCP film 1 , the second LCP film 2 , and the first metal foil 3 are stacked so that the surface of the first LCP film 1 and the surface of the second LCP film 2 directly face each other, thereby producing a stacked precursor 10 .
[0048] The first LCP film 1 and the second LCP film 2 are overlapped in such a way that the stretching direction (extrusion direction) when making the first LCP film 1 and the stretching direction (extrusion direction) when making the second LCP film 2 form an angle of 80° to 100°. Thus, the anisotropy of the orientation of the LCP laminate film can be reduced. The angle between the first LCP film 1 and the second LCP film 2 is preferably 85° to 95°, and most preferably 90°.
[0049] A schematic side view of a laminate precursor of the second embodiment is shown in Figure 3 .like Figure 3 As shown, the laminate precursor 20 may further include a second metal foil 4. In the lamination process, the surface of the first LCP film 1 and the surface of the first metal foil 3 can be arranged in a directly opposite manner. The surface of the second LCP film 2 and the surface of the second metal foil 4 can be arranged in a directly opposite manner. Thus, the laminate precursor 20 can have a structure in which the first LCP film 1 and the second LCP film 2 are sandwiched between the first metal foil 3 and the second metal foil 4.
[0050] The laminate precursors 10 and 20 may further include an LCP film (not shown) other than the first LCP film 1 and the second LCP film 2. The laminate precursors 10 and 20 may further include a metal foil (not shown) other than the first metal foil 3 and the second metal foil 4.
[0051] The laminate precursors 10 and 20 are preferably formed between mirror plates covering the LCP film surface and the metal foil surface.
[0052] The LCP applicable to the method for manufacturing the metal-clad laminate disclosed herein is not particularly limited as long as it has thermoplasticity. The LCP preferably forms an anisotropic melt at a temperature below 400°C. The first LCP and the second LCP may be made of the same material or different materials. The first LCP and the second LCP are preferably made of the same material.
[0053] A known polymer can be applied to the LCP in the method for producing the metal-clad laminate of the present invention. LCP preferably contains a p-hydroxybenzoic acid component. In addition to the p-hydroxybenzoic acid component, LCP may further contain at least one selected from the group consisting of a 4,4'-dihydroxybiphenyl (bisphenol) component, a terephthalic acid component, an isophthalic acid component, a 6-hydroxy-2-naphthoic acid component, and an ethylene terephthalate component.
[0054] For example, LCP may be a polyester containing a 6-hydroxy-2-naphthoic acid component and a p-hydroxybenzoic acid component. The 6-hydroxy-2-naphthoic acid component may be, for example, 15 mol% to 40 mol% relative to the total amount of the monomer components of the LCP. The p-hydroxybenzoic acid component may be, for example, 60 mol% to 85 mol% relative to the total amount of the monomer components of the LCP.
[0055] For example, LCP may be a polyester containing a 6-hydroxy-2-naphthoic acid component, a terephthalic acid component, and a p-hydroxybenzoic acid component. The 6-hydroxy-2-naphthoic acid component may be, for example, 15 mol% to 40 mol% relative to the total amount of the monomer components of the LCP. The terephthalic acid component may be, for example, 1 mol% to 5 mol% relative to the total amount of the monomer components of the LCP. The p-hydroxybenzoic acid component may be, for example, 65 mol% to 84 mol% relative to the total amount of the monomer components of the LCP.
[0056] For example, LCP may be a polyester containing a 4,4'-dihydroxybiphenyl component, a 6-hydroxy-2-naphthoic acid component, a terephthalic acid component, and a p-hydroxybenzoic acid component. The 4,4'-dihydroxybiphenyl component may be, for example, 5 mol% to 25 mol% relative to the total amount of the monomer components of the LCP. The 6-hydroxy-2-naphthoic acid component may be, for example, 5 mol% to 15 mol% relative to the total amount of the monomer components of the LCP. The terephthalic acid component may be, for example, 5 mol% to 15 mol% relative to the total amount of the monomer components of the LCP. The p-hydroxybenzoic acid component may be, for example, 50 mol% to 80 mol% relative to the total amount of the monomer components of the LCP.
[0057] LCP can be produced by a known method. A commercially available LCP can be used.
[0058] The melting point of each LCP is preferably in the range of 270° C. to 340° C. For example, it can be measured by differential scanning calorimetry (DSC) at a temperature increase rate of 10° C. / min, and the endothermic peak temperature during melting is defined as the melting point. The glass transition temperature of each LCP is preferably in the range of 150° C. to 250° C. The glass transition temperature can be measured by differential scanning calorimetry (DSC) at a temperature increase rate of 10° C. / min, and the endothermic peak temperature during phase change is defined as the glass transition temperature.
[0059] When the metal-clad laminate manufactured by the manufacturing method of the metal-clad laminate disclosed in the present invention is used for a flexible printed substrate, the thickness of the LCP film is preferably 20 μm or more, more preferably 25 μm or more. The thickness of the LCP film is preferably 200 μm or less, more preferably 100 μm or less. For example, the thickness of any 10 points can be measured by an electronic thickness meter, and the average value thereof is taken as the thickness of the LCP film.
[0060] When the metal-clad laminate manufactured by the manufacturing method of the metal-clad laminate disclosed in the present invention is used for a rigid printed circuit board, a thicker LCP film can be used for the purpose of advantageously expressing high-frequency characteristics. The manufacturing method of the metal-clad laminate disclosed in the present invention can be applied even to thick LCP films. For example, even if the thickness of the LCP film is 500 μm to 1000 μm, the manufacturing method of the metal-clad laminate disclosed in the present invention can be stably applied. In order to improve thickness accuracy and tensile strength and further improve dimensional stability, a rigid printed circuit board can be made by sandwiching glass cloth between two LCP films. As glass cloth, commercial products with a thickness of 40 μm to 200 μm can be used.
[0061] The first metal foil and the second metal foil may be made of the same material or different materials. The first metal foil and the second metal foil are preferably made of the same material.
[0062] The material of the metal foil of the present disclosure is not particularly limited, and examples thereof include copper, gold, silver, nickel, aluminum, and stainless steel. From the viewpoints of conductivity, operability, and cost, copper foil and stainless steel (registered trademark) foil are preferably used as the metal foil. In addition, as the copper foil, copper foil manufactured by a rolling method (rolled copper foil) and copper foil manufactured by an electrolytic method (electrolytic copper foil) can be used.
[0063] In addition, the metal foil may be subjected to chemical treatment, such as acid cleaning of the copper foil. In addition, the thickness of the metal foil is preferably 3 μm or more and 40 μm or less, and more preferably 10 μm or more and 20 μm or less. If the thickness of the metal foil is too thin, the metal foil may be deformed such as wrinkles during the manufacturing process of the metal-clad laminate. If the thickness of the metal foil is too thick, for example, when used as a flexible wiring board, the bending performance may be reduced.
[0064] The surface roughness of the metal foil in contact with the LCP film is small (i.e., low roughness), and the ten-point average roughness Rzjis is preferably less than 1.5 μm, and more preferably greater than 0.1 μm and less than 1.5 μm. Even with such a low roughness, since the metal-clad laminate disclosed in the present invention is manufactured by a specific manufacturing method, it is possible to suppress the generation of bubbles while improving the adhesion strength. In addition, if the ten-point average roughness Rzjis is, for example, less than 0.1 μm, it is difficult to ensure the stability of the adhesive force. If the ten-point average roughness Rzjis is greater than 1.5 μm, it is difficult to exhibit good high-frequency characteristics. In particular, from the perspective of the balance between high-frequency characteristics and adhesion strength, it is more preferably in the range of greater than 0.1 μm and less than 1.2 μm, and more preferably in the range of greater than 0.3 μm and less than 1.0 μm.
[0065] The ten-point average roughness Rzjis can be measured by a method in accordance with JIS B0601.
[0066] In addition, from the viewpoint of obtaining good high-frequency characteristics, the thickness of the metal foil and its surface roughness are preferably in a predetermined relationship. For example, the ratio of the thickness of the metal foil to the ten-point average roughness (unit: μm) is preferably (thickness of the metal foil) / (ten-point average roughness) = 400 / 1 to 30 / 1, and more preferably 200 / 1 to 40 / 1.
[0067] The laminate precursor 10 and the laminate precursor 20 may be produced using a mold described later.
[0068] The method for manufacturing a metal-clad laminate disclosed in the present invention includes a heating step, after the lamination step is completed, heating the laminate precursor at a temperature 15°C to 45°C higher than a first melting point for 1 minute to 60 minutes in an environment with a vacuum degree of 200 hPa or less, wherein the first melting point is the higher melting point of the first liquid crystal polymer film and the second liquid crystal polymer film. The method for manufacturing a metal-clad laminate disclosed in the present invention can be performed by a vacuum laminator.
[0069] The heating temperature is a temperature 15°C higher than the first melting point (first melting point + 15°C) or more, preferably a temperature 20°C higher than the first melting point (first melting point + 20°C) or more, wherein the first melting point is the highest melting point among the melting points of the multiple LCP films laminated. In addition, the heating temperature is a temperature 45°C higher than the first melting point (first melting point + 45°C) or less, preferably a temperature 40°C higher than the first melting point (first melting point + 40°C) or less. If the heating temperature is less than a temperature 15°C higher than the first melting point, the anisotropy (MD / TD) of the orientation of the LCP laminated film becomes larger. In addition, the bonding strength between the LCP film and the metal foil becomes lower. In addition, the difference in the linear expansion coefficients of MD and TD becomes larger. Furthermore, the LCP laminated film produces voids, the resin strength decreases, and the metal-coated laminate becomes prone to warping. On the other hand, if the heating temperature is greater than a temperature 45°C higher than the first melting point, it is difficult to control the orientation of the LCP laminated film. In addition, wrinkles are generated in the metal-clad laminate, and thickness control becomes difficult. MD and TD described here are directions based on one of the laminated LCP films.
[0070] The heating rate is preferably 1° C. / min to 50° C. / min, more preferably 2° C. / min to 20° C. / min, and even more preferably 5° C. / min to 15° C. / min.
[0071] The heating time of the above-mentioned heating temperature range is more than 1 minute, preferably more than 2 minutes, and more preferably more than 5 minutes. The heating time of the above-mentioned heating temperature range is less than 60 minutes, preferably less than 30 minutes, and more preferably less than 20 minutes. If the heating time is short, the anisotropy of the orientation becomes high. The bonding strength between the LCP film and the metal foil is reduced. The resin strength of the LCP laminated film is also reduced. On the other hand, if the heating time is long, the molecular weight increases, the viscosity changes, and then the mechanical properties change.
[0072] The heating temperature can be considered to be equal to the set temperature of the heater, which is a heater in contact with the mirror plate surface sandwiching the laminated precursor. The heater is not particularly limited as long as it can heat the laminated precursor. As the heater, for example, an oil heater, an electric heater, a thin planar heater, etc. can be used.
[0073] The heating step is performed in an environment with a vacuum degree of 200 hPa or less. That is, the vacuum degree in the press machine that presses the laminate precursor is 200 hPa or less. The vacuum degree is preferably 100 hPa or less, more preferably 50 hPa or less, and further preferably 20 hPa or less. The vacuum degree may be 0.1 hPa or more. If the vacuum degree is higher than 200 hPa, voids are generated in the LCP laminate film, and the resin strength of the LCP laminate film is easily reduced. Decompression may be performed simultaneously with heating. Decompression is preferably started at a temperature 20°C lower than the first melting point (first melting point -20°C) or less.
[0074] The method for producing a metal-clad laminate of the present invention includes a pressurizing step, in which cooling is started after the heating step is completed, and the laminate precursor is pressurized in a lamination direction at a first pressure of 0.5 MPa to 5 MPa. The lamination precursor is preferably pressurized (compressed) over the entire surface of the lamination precursor.
[0075] The first pressure for pressurizing the lamination precursor in the lamination direction is 0.5MPa or more, preferably 1MPa or more. The pressure for pressurizing the lamination precursor is 5MPa or less, preferably 3MPa or less. If the pressurization time is too late or the pressure is too low, the anisotropy of the orientation becomes high, the bonding strength of the metal foil becomes low, and voids are generated in the LCP laminated film, and the resin strength of the LCP laminated film decreases. If the pressurization starts too early or the pressure is too high, the anisotropy of the orientation becomes high, and the LCP laminated film is wrinkled, and the thickness of the LCP laminated film is uneven.
[0076] It is preferred that the laminate precursor is placed in a mold for molding a metal-clad laminate and the pressurizing step is performed while molding the laminate precursor. Figure 4 and Figure 5 A schematic cross-sectional view showing a laminate precursor and a mold in a press step. Figure 4 and Figure 5 The manner shown is only exemplary, and the form of the laminated precursor and the mold is not limited to Figure 4 and Figure 5 Dimensions shown are ratios. Figure 4 and Figure 5 The laminated precursor 20 is shown, but it can also be applied to the laminated precursor 10. Figure 6 and Figure 7 A laminate precursor of a multilayer structure is shown.
[0077] Figure 4In the illustrated embodiment, the laminate precursor 20 is formed in the recess 32a of the lower mold 32. The dimension of the recess 32a in the surface direction is preferably suitable for the dimension of the target metal-clad laminate. The dimension of the recess 32a in the thickness direction (depth) is preferably suitable for the thickness of the target metal-clad laminate. Preferably, the recess 32a has a depth such that when the laminate precursor 20 is pressurized by the upper mold 31, the upper surface of the second metal foil 4 of the laminate precursor 20 and the upper surface of the lower mold 32 become flush with each other (plane 1) under the condition that a prescribed pressure is applied to the laminate precursor 20.
[0078] Figure 5 In the illustrated embodiment, the depth of the concave portion 34a of the lower mold 34 is greater than or equal to the thickness of the target metal-clad laminate. The upper mold 33 has a convex portion 33a, which fits into the concave portion 34a while pressurizing the laminate precursor 20. Preferably, when the laminate precursor 20 is pressurized by the upper mold 33, the convex portion 33a fits into the concave portion 34a while a predetermined pressure is applied to the laminate precursor 20 by the convex portion 33a. Figure 5 In addition to the above, the method shown is Figure 4 The same way as shown.
[0079] The laminate precursor 20 is heated to a temperature above the melting point of the LCP film 1 and the LCP film 2 in the heating step. Therefore, the fluidity of the molten LCP film increases, and the thickness becomes easy to change by applying pressure. Therefore, the thickness can be easily controlled by using a mold, and a metal-clad laminate having a desired thickness can be manufactured, wherein the mold has a recessed portion for molding into the final size (shape) of the manufactured metal-clad laminate.
[0080] The pressurization step allows the LCP films to be welded to each other and the LCP film and the metal foil to be bonded together. In addition, the flatness of the metal-clad laminate can be improved (the amount of warpage can be reduced) and the thickness of the metal-clad laminate can be controlled.
[0081] The manufacturing method of the metal-clad laminate disclosed in the present invention includes an annealing process, in which the first pressure is reduced to a second pressure of 1 / 2 to 1 / 20 of the first pressure within a temperature range of the first glass transition temperature to the first melting point, and the state of the second pressure is maintained for 5 minutes to 60 minutes in the temperature range and the second pressure, wherein the first glass transition temperature is the lower glass transition temperature of the glass transition temperature of the first liquid crystal polymer film and the second liquid crystal polymer film. By performing the annealing process, the deformation caused by the first pressure in the pressurizing process can be alleviated. That is, the first pressure in the pressurizing process causes the laminate precursor to deform in the thickness direction, and the deformation is alleviated by reducing the first pressure to the second pressure in the annealing process. As a result, the increase in the linear expansion coefficient in the thickness direction (z direction) of the LCP laminate film can be suppressed. The heating temperature in the annealing step is preferably a temperature 5° C. to 40° C. lower than the first melting point, and more preferably a temperature 10° C. to 30° C. lower than the first melting point.
[0082] The second pressure is a pressure reduced to a range of 1 / 2 to 1 / 20 of the first pressure. For example, when the first pressure is pressurized at 1 MPa, the second pressure is set to 0.05 MPa to 0.5 MPa. The deformation in the thickness direction of the laminate caused by the pressurization process can be reduced by the annealing process. In addition, the second pressure is preferably reduced to a range of 1 / 2 to 1 / 10 of the first pressure, and more preferably reduced to a range of 1 / 2 to 1 / 5. More preferably, the state of the temperature range and the second pressure is maintained for 10 minutes to 50 minutes, and even more preferably, for 20 minutes to 40 minutes.
[0083] After the annealing step, the material is cooled to room temperature (25° C.) at a rate of 5° C. / min, and the pressure in the high-temperature press machine is returned to atmospheric pressure, thereby manufacturing a metal-clad laminate.
[0084] In the method for manufacturing a metal-clad laminate disclosed in the present invention, (1) a laminate precursor has two or more first laminate units, wherein the first laminate units laminate a second liquid crystal polymer film, a first liquid crystal polymer film, and a first metal foil in sequence, and a thin planar heater is arranged between adjacent first laminate units; or (2) a laminate precursor has two or more second laminate units, wherein the second laminate units laminate a second metal foil, a second liquid crystal polymer film, a first liquid crystal polymer film, and a first metal foil in sequence, and a thin planar heater is arranged between adjacent second laminate units and second laminate units; by using such a laminate precursor, uneven heating temperature will not occur, and a significant improvement in productivity can be achieved.
[0085] like Figure 6 As shown, the laminated precursor 30 has two or more first laminated units 7, wherein the first laminated units 7 laminate the second liquid crystal polymer film 2, the first liquid crystal polymer film 1 and the first metal foil 3 in sequence, and a thin planar heater 5 is arranged between the adjacent first laminated units 7 and the first laminated units 7. As a result, uneven heating temperature will not occur, and productivity can be greatly improved. The number of laminated layers of the first laminated unit 7 is preferably 2 or more and 100 or less, more preferably 5 or more and 50 or less, and further preferably 5 or more and 20 or less. In addition, Figure 6 Reference numeral 50 denotes a hot plate of a high temperature press machine. In addition, a mirror plate may be provided between the first metal foil 3 and the thin planar heater 5 .
[0086] like Figure 7As shown, the laminated precursor 40 has two or more second laminated units 8, and the second laminated units 8 laminate the second metal foil 4, the second liquid crystal polymer film 2, the first liquid crystal polymer film 1 and the first metal foil 3 in sequence, and a thin planar heater 5 is arranged between the adjacent second laminated units 8 and the second laminated units 8. As a result, there will be no uneven heating temperature, and the productivity can be greatly improved. The number of laminated layers of the second laminated unit 8 is preferably 2 or more and 100 or less, more preferably 5 or more and 50 or less, and further preferably 5 or more and 20 or less. In addition, Figure 7 Reference numeral 50 denotes a hot plate of a high temperature press machine. In addition, a mirror plate may be provided between the first metal foil 3 and the thin planar heater 5 and between the second metal foil 4 and the thin planar heater 5 .
[0087] The thin planar heater 5 is preferably capable of heating to 300° C. or higher (preferably 300° C. to 600° C.). The thickness of the thin planar heater 5 is preferably 3000 μm or less, and more preferably 50 μm or more and 3000 μm or less. As the thin planar heater 5 , for example, a mica-coated planar heater or a silicone-coated planar heater can be cited. The thin planar heater 5 can be used repeatedly.
[0088] use Figure 6 and Figure 7 The laminated precursor 30 and laminated precursor 40 of the multilayer structure shown are manufactured by laminating two or more laminated units through the same heating process, pressurizing process and annealing process as the manufacturing method of the metal-clad laminated body described in the first embodiment of the present disclosure. Then, each laminated unit is taken out from the metal mold to obtain a metal-clad laminated body.
[0089] According to the method for producing a metal-clad laminate of the present disclosure, it is possible to produce a metal-clad laminate having an LCP laminate film having improved anisotropy.
[0090] According to the method for producing a metal-clad laminate of the present disclosure, the step of improving anisotropy and the step of bonding the metal foil to the LCP laminate film can be performed simultaneously, thereby improving production efficiency.
[0091] The method for manufacturing a metal-clad laminated body disclosed in the present invention can produce a metal-clad laminated body having high strength and a metal-clad foil laminate having high dimensional accuracy. In addition, even if the roughness of the metal foil is reduced, the LCP laminated film and the metal foil can be bonded with high strength. Since the roughness of the metal foil can be reduced, transmission loss can be suppressed.
[0092] A metal-clad laminate according to a second embodiment of the present disclosure will be described.
[0093] The metal-clad laminate body according to the second embodiment of the present disclosure is manufactured by the method for manufacturing the metal-clad laminate body according to the first embodiment of the present disclosure.
[0094] The metal-clad laminate of the present disclosure cannot be directly defined by composition, structure, characteristics, etc., or may be completely impossible. In such cases, the metal-clad laminate of the present disclosure should be allowed to be defined by its manufacturing method.
[0095] Regarding the liquid crystal polymer film, the LCP laminate film, and the metal foil, the description of the metal-clad laminate in the first embodiment is cited.
[0096] like Figure 8 As shown, the metal-clad laminate 110 of the present disclosure includes a second liquid crystal polymer (LCP) layer 102 , a first liquid crystal polymer (LCP) layer 101 , and a first metal layer 103 in this order. The peel strength between the first liquid crystal polymer layer and the first metal layer is 0.9 kN / m to 2.5 kN / m. The orientation (MD / TD ratio) of the LCP laminate film composed of the first liquid crystal polymer layer and the second liquid crystal polymer layer is 1.0 to 1.2, and the resin strength of the LCP laminate film is 100 MPa or more, and the warpage is 3 mm or less. 2 The average number of voids having an area diameter of 0.5 mm or less is preferably 5 or less. The ratio of the linear expansion coefficients in the plane direction (MD / TD) of the LCP laminate film is preferably 1.2 or less, and the linear expansion coefficient in the thickness direction (z direction) is preferably 45 ppm or less.
[0097] like Fig. 9 As shown, the metal-clad laminate 120 of the present disclosure includes a second metal layer 104 , a second liquid crystal polymer (LCP) layer 102 , a first liquid crystal polymer (LCP) layer 101 , and a first metal layer 103 in this order. The peel strength between the first liquid crystal polymer layer and the first metal layer is 0.9 kN / m to 2.5 kN / m. The peel strength between the second liquid crystal polymer layer and the second metal layer is 0.9 kN / m to 2.5 kN / m. The orientation (MD / TD ratio) of the LCP laminate film composed of the first liquid crystal polymer layer and the second liquid crystal polymer layer is 1.0 to 1.2, and the resin strength of the LCP laminate film is 100 MPa or more, and the warpage is 3 mm or less. 2 The average number of voids having an area diameter of 0.5 mm or less is preferably 5 or less. The ratio of the linear expansion coefficients in the plane direction (MD / TD) of the LCP laminate film is preferably 1.2 or less, and the linear expansion coefficient in the thickness direction (z direction) is preferably 45 ppm or less.
[0098] The first metal layer and the second metal layer are preferably electrolytic copper layers or rolled copper layers having a thickness of 3 μm to 40 μm.
[0099] In the metal-clad laminate of the second embodiment, the peel strength between the LCP laminate film and the metal foil can be 0.9 kN / m to 2.5 kN / m. The peel strength is preferably 1.0 kN / m to 2.0 kN / m. For a test piece of 50 mm in length and 10 mm in width, the metal foil is peeled off from the LCP laminate film at a peeling speed of 50 mm / min and a peeling angle of 90° starting from the end of the short side according to the method specified in JIS K6854-1, and the peel strength can be measured.
[0100] In the metal-clad laminate of the second embodiment, the resin strength of the LCP laminate film from which the metal foil is removed may be 100 MPa or more. The resin strength is preferably 100 MPa to 400 MPa. The metal foil (copper foil) may be removed by an aqueous solution of ferric chloride. The LCP laminate film can be cut into a test piece shape based on JIS K7124-5, and the resin strength can be measured at a tensile speed of 12.5 mm / min.
[0101] In the metal-clad laminate of the second embodiment, the ratio of the linear expansion coefficients in the plane direction (MD / TD) of the LCP laminate film without the metal foil is preferably 1.2 or less, more preferably 0.9 to 1.2, and further preferably 1.0 to 1.2. The metal foil (copper foil) can be removed by an aqueous ferric chloride solution. The linear expansion coefficients of MD and TD in the range of 50°C to 150°C can be measured by the stretching mode of thermomechanical analysis (TMA) at a heating rate of 10°C / min, and the ratio of the linear expansion coefficients in the plane direction can be calculated from the ratio of MD to TD. MD and TD related to the linear expansion coefficients in the plane direction represent the directions based on the uppermost LCP laminated film in the laminated LCP laminated films.
[0102] In the metal-clad laminate of the second embodiment, the coefficient of linear expansion in the thickness direction (z direction) of the LCP laminated film without the metal foil is preferably 45 ppm or less, more preferably 40 ppm or less, and further preferably 35 ppm or less. The metal foil (copper foil) can be removed by an aqueous solution of ferric chloride. The coefficient of linear expansion in the thickness direction (z direction) of the LCP laminate film can be measured by thermomechanical analysis (TMA) in compression mode at a heating rate of 10°C / min in a temperature range of 50°C to 150°C.
[0103] In the metal-clad laminate of the second embodiment, the LCP laminated film from which the metal foil has been removed preferably does not have the presence of voids and wrinkles. The voids and wrinkles can be confirmed by observing the LCP laminated film from which the metal foil has been dissolved and removed using a stereomicroscope, etc. The metal foil (copper foil) can be removed by an aqueous solution of ferric chloride. LCP laminated film per 10cm 2 The average number of voids having an area diameter of 0.5 mm or less is preferably 5 or less, more preferably 3 or less, and most preferably 0.
[0104] In the metal-clad laminate of the second embodiment, the warping degree of the metal-clad laminate is suppressed. When a 40 mm × 40 mm metal-clad laminate is placed on a flat glass plate, the height (warping amount) on the diagonal glass plate when one corner is pressed is 3 mm or less, preferably 2 mm or less, more preferably 1 mm or less, and further preferably 0.1 mm to 1 mm.
[0105] The metal-clad laminate disclosed in the present invention is suitable for use in a flexible printed circuit board or a rigid printed circuit board. Example
[0106] Hereinafter, the metal-clad laminate and the method for producing the same according to the present disclosure will be described using examples. The metal-clad laminate and the method for producing the same according to the present disclosure are not limited to the following examples.
[0107] <Melting Point and Glass Transition Temperature> The temperature was measured by differential scanning calorimetry (DSC) at a temperature increase rate of 10° C. / min, and the endothermic peak temperature during melting was defined as the melting point of the LCP film. The temperature was measured by differential scanning calorimetry (DSC) at a temperature increase rate of 10° C. / min, and the endothermic peak temperature during phase change was defined as the glass transition temperature of the LCP film.
[0108] <Ten-point average roughness> The ten-point average roughness of the electrolytic copper foil was measured using a contact-type surface roughness meter (manufactured by Midoyo Co., Ltd., model: SJ-201).
[0109] (Production Example 1) -Production of LCP film 1- 27 mol% of 6-hydroxy-2-naphthoic acid, 73 mol% of p-hydroxybenzoic acid, and 102 mol% of acetic anhydride were placed in a reaction vessel equipped with a distillation tube, and heated to 170°C over 1 hour in a nitrogen atmosphere, maintained at 170°C for 30 minutes, and then heated to 330°C over 7 hours. After further reacting at 330°C for 10 minutes, the pressure was reduced at 330°C. Next, the pressure was reduced to 10 Torr over 1.5 hours, and the polycondensation was completed when a predetermined stirring torque was reached, thereby obtaining a thermoplastic liquid crystal polymer 1 (LCP1). The obtained thermoplastic liquid crystal polymer 1 (LCP1) was heated and kneaded at 280°C to 300°C using a twin-screw extruder, and extruded through a T-die with a diameter of 40 mm and a slit spacing of 0.5 mm to obtain a 50 μm thick LCP film 1. The melting point Tm of the LCP film 1 was 282°C, and the glass transition temperature was 230°C.
[0110] (Production Example 2) -Production of LCP film 2- In Production Example 1, except that 19 mol % of 6-hydroxy-2-naphthoic acid, 81 mol % of p-hydroxybenzoic acid, 1 mol % of terephthalic acid, and 102 mol % of acetic anhydride were put into a reaction vessel equipped with a distillation tube, a thermoplastic liquid crystal polymer 2 (LCP2) was synthesized in the same manner as in Production Example 1 to prepare an LCP film 2. The melting point Tm of the LCP film 2 was 310° C., and the glass transition temperature was 200° C.
[0111] (Production Example 3) -Production of LCP film 3- In Production Example 1, except that 10 mol % of 6-hydroxy-2-naphthoic acid, 65 mol % of p-hydroxybenzoic acid, 10 mol % of terephthalic acid, 15 mol % of 4,4'-dihydroxybiphenyl, and 102 mol % of acetic anhydride were put into a reaction vessel equipped with a distillation tube, a thermoplastic liquid crystal polymer 3 (LCP3) was synthesized in the same manner as in Production Example 1 to prepare an LCP film 3. The melting point Tm of the LCP film 3 was 325°C, and the glass transition temperature was 230°C.
[0112] (Test Example 1) -Manufacturing of Metal-clad Laminated Body- An electrolytic copper foil (10-point average roughness (Rzjis): 0.9 μm) with a length of 300 mm, a width of 300 mm, and a thickness of 12 μm was placed as the first metal foil on a 3 mm mirror plate. The surface of the first metal foil having the above average roughness was arranged to face the opposite side of the mirror plate. Next, the LCP film 1 having a thickness of 50 μm, a length of 300 mm, and a width of 300 mm prepared as described above was placed on the first metal foil as a first LCP film. Next, the LCP film 1 having a thickness of 50 μm, a length of 300 mm, and a width of 300 mm was placed as a second LCP film on the first LCP film. The second LCP film was arranged so that the extrusion direction of the first LCP film and the extrusion direction of the second LCP film formed a 90° angle. Next, an electrolytic copper foil (10-point average roughness (Rzjis): 0.9 μm) with a length of 300 mm, a width of 300 mm, and a thickness of 12 μm was placed as a second metal foil on the second LCP film. The surface of the second metal foil having the above average roughness was arranged to face the second LCP film. Next, a 3 mm mirror plate was placed on the second metal foil. A laminate precursor was produced as described above. The laminate precursor was placed between upper and lower hot plates of a high-temperature press capable of reducing pressure.
[0113] The pressure in the high-temperature press is reduced to a vacuum degree of 10 hPa. In addition, the temperature is increased at 10°C / min while the pressure is reduced, and the heating temperature of the laminate precursor is increased to 300°C. Maintain it at 300°C (maximum heating temperature) for 5 minutes (heating process). After the heating process is completed, cooling is started at a rate of 5°C / min, and then the laminate precursor is immediately pressurized at a pressure of 1 MPa in the lamination direction (pressurization process). Next, the temperature was cooled at a rate of 5°C / min, and when the heating temperature reached 270°C, the pressure was reduced to 0.5 MPa, and the heated and pressurized state was maintained for 30 minutes (annealing step). After that, the temperature was cooled to room temperature (25°C) at a rate of 5°C / min, and the pressure in the high-temperature press was returned to atmospheric pressure to produce a metal-clad laminate.
[0114] (Test Example 2 to Test Example 20) -Manufacturing of Metal-clad Laminated Body- In Test Example 1, metal-clad laminates of Test Examples 2 to 20 were produced in the same manner as in Test Example 1 except that the conditions were changed to those shown in Tables 1 to 5. In addition, "in the heating step" in "pressing start time in the pressurizing step" of Test Example 20 means that pressurizing starts before the end of the heating step. "Heating step" means the step from reaching the maximum heating temperature to starting cooling. If pressure is applied during the "heating process", there is a problem that the molten LCP will flow excessively due to the pressure applied when the volume of the LCP is the largest. Therefore, it is necessary to start cooling after the "heating process" and apply pressure when the volume of the LCP begins to shrink. Applying pressure before cooling is the same as "during the heating process".
[0115] Next, the orientation of the laminate film (MD / TD ratio), the peel strength of the metal-clad laminate, the resin strength of the laminate film, the linear expansion coefficient of the laminate film (MD / TD ratio), the linear expansion coefficient of the laminate film (z direction), the voids of the laminate film, the wrinkles of the laminate film, the warping of the metal-clad laminate, and the thickness accuracy of the laminate film were evaluated as follows. The results are shown in Tables 1 to 5. In the following, MD and TD represent the directions of the first LCP film and the second LCP film, with the second LCP film on the upper side as the reference.
[0116] <Orientation (MD / TD ratio)> The microwave transmission intensity of the sample in MD and TD was measured using a microwave cavity resonator (a microwave molecular orientation meter manufactured by Oji Testing Instruments Co., Ltd.) to determine the orientation (MD / TD ratio), wherein the LCD laminate film was obtained by removing the copper foil from each metal-clad laminate using an aqueous ferric chloride solution.
[0117] <Peel Strength> Each metal-clad laminate was cut into a test piece of 50 mm in length and 10 mm in width, and the copper foil was peeled off from the LCP laminate film from the end of the short side according to the method specified in JIS K6854-1 to measure the peel strength at a peel angle of 90° and a peel speed of 50 mm / min.
[0118] <Resin Strength> After the copper foil was removed from each metal-clad laminate with an aqueous ferric chloride solution, a 100 μm thick LCP laminate film was cut into a test piece according to the method specified in JIS K7124-5 and the resin strength was measured at a tensile speed of 12.5 mm / min.
[0119] <Linear Expansion Coefficient (MD / TD Ratio)> After removing the copper foil from each metal-clad laminate by an aqueous solution of ferric chloride, the linear expansion coefficients in MD and TD in the range of 50°C to 150°C were measured at a heating rate of 10°C / min in the tensile mode of a thermomechanical analyzer (TMA) for an LCP laminate film with a thickness of 100 μm, and the linear expansion coefficient (MD / TD ratio) was calculated.
[0120] [Linear expansion coefficient (z direction)] After removing the copper foil from each metal-clad laminate using an aqueous ferric chloride solution, the linear expansion coefficient in the lamination direction (z direction) in the range of 50°C to 150°C was measured for a 100 μm thick LCP laminate film using a thermomechanical analyzer (TMA) in compression mode at a heating rate of 10°C / min.
[0121] <Gap> After the copper foil was removed from each metal-clad laminate by an aqueous solution of ferric chloride, a test piece of 200 mm in length and 200 mm in width was cut out from the LCP laminate film of 100 μm in thickness, and the surface of the test piece was observed at a magnification of 50 times using a stereoscopic microscope (MX50, manufactured by Orionpass Co., Ltd.), and the number of microstructures per 10 cm was measured. 2 The average number of voids per area was evaluated based on the following evaluation criteria. [Evaluation criteria] A: The average number of voids with a diameter of less than 0.5 mm is 0 B: The average number of voids with a diameter of less than 0.5 mm is 1 to 5 C: The average number of voids with a diameter of less than 0.5 mm is 6 or more, or the average number of voids with a diameter greater than 0.5 mm is 1 or more
[0122] <Wrinkles> After removing the copper foil from each metal-clad laminate using an aqueous solution of ferric chloride, a test piece of 200 mm in length and 200 mm in width was cut out from the 100 μm thick LCP laminate film. The surface of the test piece was photographed using a smartphone (i-Phone 12 pro, manufactured by Apple) and observed at a magnification of 10 times. The average number of wrinkles was measured and evaluated based on the following evaluation criteria. [Evaluation criteria] A: 0 wrinkles B: 1 to 5 wrinkles with a length of 1 cm to 3 cm C: There are 1 to 5 wrinkles with a length of 1 cm to 3 cm or more than 1 wrinkle with a length greater than 3 cm
[0123] <Warping amount> A test piece of 40 mm in length and 40 mm in width cut out from each metal-clad laminate was placed on a flat glass plate, and the height (warping amount; mm) of the test piece at the diagonal position on the glass plate when one corner of the test piece was pressed was measured using a vernier caliper. Evaluation was performed based on the following evaluation criteria. [Evaluation criteria] A: 0mm or more and 3mm or less B: greater than 3mm and less than 8mm C: greater than 8mm and less than 12mm D: greater than 12mm
[0124] <Thickness Accuracy> After removing the copper foil from each metal-clad laminate with an aqueous ferric chloride solution, the thickness of the 100 μm thick LCP laminate film was measured at 10 points using an electronic thickness meter (manufactured by Midoyo Co., Ltd.), and the average value was calculated. The 10 measured thicknesses were evaluated to see whether they were within the range of ±10% of the average value.
[0125] [Table 1]
[0126] [Table 2]
[0127] [Table 3]
[0128] [Table 4]
[0129] [Table 5]
[0130] The test examples using LCP film 1 and LCP film 2, the test examples using LCP film 1 and LCP film 3, and the test examples using LCP film 2 and LCP film 3 also obtained results at the same level as those of test examples 1 to 12 in Tables 1 to 3.
[0131] According to the results of Tables 1 to 5, Test Examples 1 to 12 not only simultaneously improve anisotropy and copper-coat, but also can produce a metal-clad laminate having an LCP film, wherein the LCP film is an LCP film with improved anisotropy. In the metal-clad laminates of Test Examples 1 to 12, even without utilizing the anchoring effect of the metal foil, the bonding strength between the LCP film and the metal foil can be improved. For the laminated films in the metal-clad laminates of Test Examples 1 to 12, the generation of voids and wrinkles is suppressed, and the resin strength is high. In addition, the metal-clad laminates of Test Examples 1 to 12 can be produced with high dimensional accuracy. In addition, the metal-clad laminates of Test Examples 1 to 12 can achieve a small warpage of less than 3 mm.
[0132] The metal-clad laminate and the method for manufacturing the same are described based on the above-mentioned embodiments and examples, but are not limited to the above-mentioned embodiments and examples, and may include various deformations, changes and improvements of each disclosed element (including the elements described in the claims, the specification and the drawings) within the scope of the present invention and based on the basic technical concept of the present invention. In addition, within the scope of the claims of the present invention, various combinations, substitutions or selections may be made to each disclosed element.
[0133] Further problems, objects, and modes (including modified modes) of the present invention can also be clarified from the entire disclosure of the present invention including the claims.
[0134] Regarding the numerical range described in this specification, even if there is no special description, any numerical value or range included in the range should be interpreted as a numerical value or range specifically described in this specification.
[0135] The above-mentioned embodiments may be described in part or in whole as in the following supplementary notes, but are not limited to the following description. Each supplementary note may be combined with each claim described in the patent claims. [Supplementary Note 1] A metal-clad laminate produced by the method for producing a metal-clad laminate of the present disclosure. [Supplementary Note 2] A metal-clad laminate in which a first metal foil and an LCP laminate film are laminated. Industrial Applicability
[0136] The method for producing a metal-clad laminate of the present disclosure can be applied to, for example, the production of a metal-clad laminate used in electronic devices requiring high-frequency characteristics and low dielectric properties. The metal-clad laminate disclosed in the present invention has high bonding strength and resin strength, high dimensional accuracy, little void generation, and small warpage, and is therefore suitable for use in the production of high-quality flexible printed circuit boards or rigid printed circuit boards, for example. [Explanation of symbols]
[0137] 1The first LCP film 2. Second LCP film 3. First Metal Foil 4 Second metal foil 5 Thin planar heater 7 First stacking unit 8 Second stacking unit 10 Lamination Precursor 20 Lamination Precursor 30 Lamination Precursor 31, 33 upper mold 32, 34 lower die 33a convex part 32a, 34a recessed parts 40 Lamination Precursor 50 Hot Plate 101 First LCP Layer 102 Second LCP layer 103 First Metal Layer 104 Second Metal Layer 110 Metal-clad laminate 120 Metal-clad laminate
Claims
1. A method for producing a metal-clad laminate, wherein: The method comprises: a lamination step of laminating a lamination precursor of a first liquid crystal polymer film, a second liquid crystal polymer film, and a first metal foil in such a manner that a surface of the first liquid crystal polymer film and a surface of the second liquid crystal polymer film are directly opposed to each other; A heating step of heating the laminate precursor at a temperature 15° C. to 45° C. higher than a first melting point for 1 minute to 60 minutes under a vacuum degree of 200 hPa or less, wherein the first melting point is a higher melting point of the first liquid crystal polymer film and the second liquid crystal polymer film; A pressurizing step, after the heating step is completed, cooling is started, and the lamination precursor is pressurized in a lamination direction at a first pressure of 0.5 MPa to 5 MPa, In the lamination step, the first liquid crystal polymer film and the second liquid crystal polymer film are laminated so that the extending direction of the first liquid crystal polymer film and the extending direction of the second liquid crystal polymer film form an angle of 80° to 100°.
2. The method for producing a metal-clad laminate according to claim 1, wherein: The method includes an annealing process, in which the first pressure is reduced to a second pressure of 1 / 2 to 1 / 20 of the first pressure within a temperature range of a first glass transition temperature to a first melting point, and the temperature range and the second pressure are maintained for 5 to 60 minutes, wherein the first glass transition temperature is the lower glass transition temperature of the glass transition temperatures of the first liquid crystal polymer film and the second liquid crystal polymer film.
3. The method for producing a metal-clad laminate according to claim 1, wherein: The melting points of the first liquid crystal polymer film and the second liquid crystal polymer film are 270° C. to 340° C., respectively.
4. The method for producing a metal-clad laminate according to claim 1, wherein: The first liquid crystal polymer film and the second liquid crystal polymer film have the same material.
5. The method for producing a metal-clad laminate according to claim 1, wherein: The ten-point average roughness of the surface of the first metal foil facing the first liquid crystal polymer film is 1.5 μm or less.
6. The method for producing a metal-clad laminate according to claim 1, wherein: The first metal foil is an electrolytic copper foil or a rolled copper foil having a thickness of 3 μm to 40 μm.
7. The method for producing a metal-clad laminate according to claim 1, wherein: In the manufactured metal-clad laminate, the peel strength between the first liquid crystal polymer film and the first metal foil is 0.9 kN / m to 2.5 kN / m.
8. The method for producing a metal-clad laminate according to claim 1, wherein: In the lamination step, the lamination precursor is manufactured in a mold; In the pressurizing step, the laminate precursor is pressurized while being molded by the mold.
9. The method for producing a metal-clad laminate according to claim 1, wherein: The laminate precursor further comprises a second metal foil, In the lamination step, the surface of the first liquid crystal polymer film and the surface of the first metal foil are arranged so as to directly face each other. The surface of the second liquid crystal polymer film and the surface of the second metal foil are arranged so as to directly face each other.
10. The method for producing a metal-clad laminate according to claim 9, wherein: The second metal foil is an electrolytic copper foil or a rolled copper foil having a thickness of 3 μm to 40 μm. The ten-point average roughness of the surface of the second metal foil facing the second liquid crystal polymer film is 1.5 μm or less.
11. The method for producing a metal-clad laminate according to claim 9, wherein: In the manufactured metal-clad laminate, the peel strength between the second liquid crystal polymer film and the second metal foil is 0.9 kN / m to 2.5 kN / m.
12. The method for producing a metal-clad laminate according to any one of claims 1 to 8, wherein: The laminate precursor has two or more first laminate units, wherein the first laminate unit laminates a second liquid crystal polymer film, a first liquid crystal polymer film, and a first metal foil in this order. A thin planar heater is disposed between the adjacent first stacking units.
13. The method for producing a metal-clad laminate according to any one of claims 9 to 11, wherein: The laminate precursor has two or more second laminate units, wherein the second laminate unit laminates a second metal foil, a second liquid crystal polymer film, a first liquid crystal polymer film, and a first metal foil in this order. A thin planar heater is disposed between the adjacent second stacking units.
14. The method for producing a metal-clad laminate according to claim 12, wherein: The thin planar heater can be heated to a temperature of 300° C. or higher.
15. A metal-clad laminate, characterized in that: The invention sequentially comprises a second liquid crystal polymer layer, a first liquid crystal polymer layer and a first metal layer, The peel strength between the first liquid crystal polymer layer and the first metal layer is 0.9 kN / m to 2.5 kN / m, The orientation (MD / TD ratio) of the laminated film composed of the first liquid crystal polymer layer and the second liquid crystal polymer layer is 1.0 to 1.2, and the resin strength of the laminated film is 100 MPa or more, The warping amount is less than 3 mm.
16. A metal-clad laminate, characterized in that: The invention sequentially comprises a second metal layer, a second liquid crystal polymer layer, a first liquid crystal polymer layer and a first metal layer, The peel strength between the first liquid crystal polymer layer and the first metal layer is 0.9 kN / m to 2.5 kN / m, The peel strength between the second liquid crystal polymer layer and the second metal layer is 0.9 kN / m to 2.5 kN / m, The orientation (MD / TD ratio) of the laminated film composed of the first liquid crystal polymer layer and the second liquid crystal polymer layer is 1.0 to 1.2, and the resin strength of the laminated film is 100 MPa or more, The warping amount is less than 3 mm.
17. The metal-clad laminate according to claim 15 or 16, wherein: The laminated film has a thickness of 10 cm 2 The average number of voids having an area diameter of 0.5 mm or less is 5 or less.
18. The metal-clad laminate according to claim 15 or 16, wherein: The ratio of the linear expansion coefficients in the plane direction (MD / TD) of the laminated film is 1.2 or less, and the linear expansion coefficient in the thickness direction (z direction) is 45 ppm or less.
19. The metal-clad laminate according to claim 15 or 16, wherein: The first metal layer and the second metal layer are electrolytic copper layers or rolled copper layers having a thickness of 3 μm to 40 μm.
20. The metal-clad laminate according to claim 15 or 16, wherein The metal-clad laminate is used for a flexible printed substrate or a rigid printed substrate.
Citation Information
Patent Citations
Polyaxial oriented high-performance laminate consisting of monoaxial oriented sheet of thermotropic liquid-crystal polymer
JP1983031718A
Method for producing metal-clad laminate, and metal-clad laminate
WO2017154811A1